Transformation of the content of the concept of «employment» in modern economic and information conditions - Tikhonova, Lyudmila E.; Jing, Li (Journal of the Belarusian State University. Economics, 2024)
The article reflects the necessity of transforming the content of the concept of «employment» due to significant changes in economic conditions and the inconsistency of the classical concept of this term with the current stage of socio-economic development of the labour market. The approaches of various researchers to the definition of employment are studied, its main forms are established, key non-standard variants employment and the changes that have occurred in the field of labour organisation in the last decade are revealed. The interpretation of the concept of «employment» formulated taking into account modern economic and information conditions and implying any options of communication and forms of labour organisation not prohibited by law is proposed.